2013
DOI: 10.1186/2191-0855-3-66
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of engineered Escherichia coli biofilms for enzymatic biosynthesis of l-halotryptophans

Abstract: Engineered biofilms comprising a single recombinant species have demonstrated remarkable activity as novel biocatalysts for a range of applications. In this work, we focused on the biotransformation of 5-haloindole into 5-halotryptophan, a pharmaceutical intermediate, using Escherichia coli expressing a recombinant tryptophan synthase enzyme encoded by plasmid pSTB7. To optimise the reaction we compared two E. coli K-12 strains (MC4100 and MG1655) and their ompR234 mutants, which overproduce the adhesin curli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
3
33
0
1
Order By: Relevance
“…The biotransformation experiment with planktonic cells was conducted by using a previously described method with slight modifications . The overnight cultures grown in LB media at 37 °C were inoculated in M9 minimal media or 50 % LB media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biotransformation experiment with planktonic cells was conducted by using a previously described method with slight modifications . The overnight cultures grown in LB media at 37 °C were inoculated in M9 minimal media or 50 % LB media.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of tryptophan was quantified by using HPLC (Shimadzu, Singapore) equipped with a ZORBAX (SB‐C18 4.6 mm×15 cm) column. A mixture of methanol (solvent A) and water (solvent B) was applied as the mobile phase (1 mL min −1 at 30 °C) with controlled gradients as follows: 0–0.5 min, 0–10 % A; 0.5–12.5 min, 10–90 % A; 15–16 min, 90–10 % A; 16–21 min, 10 % A . The mobile phase was acidified with 0.1 % formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Because of their resistance to sanitizing agents and consequent involvement in many infections or contaminations, biofilms are generally perceived negatively 4 . However, properties such higher resistance to toxic chemicals, have been exploited in biotechnological processes as biofilm cells can survive the unfavorable environment, from a biological standpoint, that various chemical reactions require 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, curli expression is triggered at low osmolality as controlled by the OmpR/EnvZ systems 16 , is stationary phase dependent as controlled by the  factor RpoS 17 and is under regulation by CpxA/CpxR that are involved in the response of cellular proteins to acidic pH 18,19 . OmpR binds the csgDEFG operon positively controlling curli expression 20 and the specific mutation of this gene ompR234 (G to T at position 43 of OmpR, corresponding leucine to arginine substitution) has been shown to increase E. coli adhesion to abiotic surfaces through increased curli production 6,[20][21][22][23] . We have chosen to use in this work E. coli MG1655 as it is a widely used curli non-producing strain whereas mutants producing curli through overexpression of ompR and csgD have been prepared.…”
Section: Introductionmentioning
confidence: 99%
“…methods was found to rapidly generate robust biocatalytic biofilms (Tsoligkas et al 2012); subsequent work focused on optimising the tryptophan synthase reaction (Perni et al 2013) and revealed that enzyme turnover was at least partially responsible for the improved biocatalytic potential of biofilms (Tong et al 2016).…”
mentioning
confidence: 99%